Infarktdiagnostik beim kritisch kranken, beatmeten Patienten = Diagnosis of myocardial infarction in critically ill, ventilated patients - Vafaie, Mehrshad; Stoyanov, Kiril M.; Giannitsis, Evangelos (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2019)
Elevated cardiac troponin values are frequently observed in critically ill patients. These are often not due to myocardial infarction (MI) but caused by various other etiologies of myocardial injury. Understanding the etiology of any troponin elevation is of enormous importance for management and therapy. According to the fourth version of the Universal Definition of MI, myocardial injury is present if at least one troponin value is above the 99th percentile upper reference limit and considered acute, when a rise and/or fall occurs. Patients with acute MI are a subgroup of patients with acute myocardial injury, who present in an ischemic clinical context. Variables defining the clinical criteria of MI include symptoms of ischemia, presumably new electrocardiographic (ECG) changes or imaging evidence of new loss of viable myocardium or regional wall motion abnormalities, or detection of an intracoronary thrombus. In critically ill or mechanically ventilated patients, the diagnosis of MI is challenging due to limitations in history taking, co-existence of comorbidities, overlapping symptoms and equivocal or unspecific ECG changes. This article presents the diagnostic criteria of the Universal MI definition, discusses subtypes of MI and focuses on various differential diagnoses. Furthermore, implications of diagnosis of MI in critically ill patients, especially regarding the use of ECG and troponin assays, are discussed.
Gesehen am 23.09.2019